The Tripartite Regulation Game of Carbon Financial Products Based on the Prospect Theory - Yu, Xiaoran; Dong, Guanglong; Liu, Changyu (Frontiers in Environmental Science, 2020)
Because of the high information asymmetry of carbon financial products (CFPs), financial institutions infringing on the rights of investors occurred worldwide. However, few studies focused on how to protect investors effectively. In this paper, from the perspective of regulation, we analyze the game relationships among governments, financial institutions, and investors. Following this, the tripartite regulation game of CFPs is further constructed. Meanwhile, centered on the heterogeneity and bounded rationality, we divide participants in this game into two types: tough or weak ones, the strategies for different types of game players are compared based on prospect theory. Moreover, through discussion the deterrence equilibrium, challenge equilibrium, and separation equilibrium, the crucial influencing factors of behavioral strategy are explored separately. Finally, some countermeasures of CFPs are put forward for governments to design appropriate regulation policies.